The impact of public debt and monetary policy on economic stability: Evidence from 30 Asian economies over two decades - Nguyen, Tiep Anh; Le, Anh Hoang (Journal of Social Economics Research, 2026)
The objective of this study was to examine the impact of public debt and monetary policy on economic stability in Asia. Economic stability here is defined by growth stability and inflation. Using panel data from 30 Asian economies for the period from 2004 to 2024, we applied a Panel Vector Autoregression (PVAR) technique to explore the dynamic links among these policy tools and macroeconomic performance over time. The impulse response function (IRF) analysis reveals that monetary policy, through lending interest rates, has a strong and sustained negative impact on economic stability in the long run, with response coefficients ranging from -0.5 to -0.6 percentage points from the 6th to 10th periods, stabilizing at approximately -0.5 percentage points from the 8th period onward. Public debt exhibits an inverted U-shaped nonlinear relationship with economic stability, showing a positive stimulative effect in the short term (first 2-3 years) but reversing to negative from the 4th to 5th year onward. Both policy instruments also significantly affect inflation, with peak impacts of approximately 6-7 percentage points in the second period. However, the inflation channel is not the primary transmission mechanism to economic stability, as the direct effects through investment and credit channels are more substantial. Based on the research results, we propose policy implications for economic stability in Asian countries.